On Roeweriella balcanica, a mysterious species of Marpissa from the Balkan Peninsula (Araneae, Salticidae) - Logunov, Dimitri V. (Arachnologische Mitteilungen, 2009)

(untitled)
The taxonomic position of the poorly known species Roeweriella balcanica Kratochvíl, 1932 from Croatia is discussed. The species is illustrated and re-described on the basis of the female holotype. The genus Roeweriella Kratochvíl, 1932 (type species: R. balcanica Kratochvíl, 1932 by monotypy) is synonymized with Marpissa C.L. Koch, 1846, and therefore the new combination, Marpissa (Marpissa) balcanica (Kratochvíl, 1932) comb.nov., is proposed.